Sphingosine-1-phosphate and vascular disease in the general population. (June 2022) - Rotheudt, Luisa; Moritz, Eileen; Markus, Marcello R.P.; Albrecht, Diana; Völzke, Henry; Friedrich, Nele; Schwedhelm, Edzard; Daum, Günter; Schminke, Ulf; Felix, Stephan B.; Rauch, Bernhard H.; Dörr, Marcus; et al.
Abstract: Background and aims: Sphingosine-1-phosphate (S1P) is a sphingolipid which influences the immune and vascular system. The relationship between S1P and vascular disease in the general population is currently unclear. We explored the relation between S1P and vascular markers, (i.e. ankle-brachial index (ABI), carotid intima-media thickness (cIMT), presence of carotid atherosclerotic plaques and brachial artery flow-mediated dilation (FMD). Methods: S1P was measured by liquid chromatography-tandem mass spectrometry in the population-based Study of Health in Pomerania (SHIP-TREND-0). Subjects with prevalent cancer, severe renal insufficiency, history of myocardial infarction and extreme values for S1P were excluded. Sex stratified linear regression models adjusted for age, smoking and waist-to-hip ratio were used. Results: A total of n = 3643 participants (52% women, median age 51, 25th and 75th percentiles 39 and 63 years) were included. In men, a 1 standard deviation higher S1P concentration was associated with a significantly greater cIMT (β: 0.0057 95%-confidence interval [CI]: 0.00027–0.0112 mm; p = 0.04) and a lower ABI (β: -0.0090 95% CI: -0.0153 to −0.0029; p < 0.01). In women, S1P was also positively associated with cIMT (β: 0.0044 95% CI: 0.0001–0.0086 mm; p = 0.04). Conclusions: We found that S1P was positively related to a greater cIMT in both sexes and a lower ABI in men. There was no association of S1P with any of the other investigated markers. Future studies are warranted to assess the suitability of S1P as a biomarker for vascular disease. Graphical abstract: Image 1 Highlights: S1P was positively related to a greater cIMT in both sexes and a lower ABI in men. Lower levels of S1P could be associated with a higher vascular disease burden by disturbing endothelial integrity. Higher S1P might represent a compensatory atheroprotective mechanism. Higher S1P levels could represent a pro-proliferative and -migrative signal for smooth muscle cells as in cIMT. Acute changes in circulating S1P in pathological situations may be responses-to-injury to support the body's ability to heal. Long-term adjustments may reflect vascular health and likely change because of the inflammatory status of vascular diseases. Sex hormones have an influence, but the precise role is currently unclear.